Internship Information System at PT Biro Klasifikasi Indonesia Samarinda Branch - Lantiur Siregar; Suci Ramadhani; Yulianto (TEPIAN, 2024)
The rapid development of information technology has led almost all companies and certain sectors to desire that all processes in their offices become fast and practical, including the internship application and registration process. PT Biro Klasifikasi Indonesia, Samarinda Branch, is a company that utilizes information technology; however, there are still aspects of information technology use that are not yet effective and efficient. One such aspect is the student internship registration, which is still done by registering directly at the company. This process is quite time-consuming and has many weaknesses. These weaknesses include long processing times and inadequate accuracy, such as incomplete or lost documents upon receipt, which can disadvantage applicants. As a result, this registration system poses difficulties for prospective interns outside the area. Therefore, the purpose of designing and developing a web-based internship information system at PT Biro Klasifikasi Indonesia Samarinda Branch is to simplify the internship registration process and assist the admin in verifying registration status, managing certificate data, and making it easier for applicants to fill out the registration form, view registration results, and check registration status through the website. The system development method used in this research is the waterfall model. To implement this internship registration information system, supporting components must function properly. These components use the Laravel framework and MySQL database. The results of this research, based on black box testing and respondent questionnaires, indicate that all features of this web-based internship information system can be used effectively and function as intended, thereby helping users manage internship registration.